Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Karyawan - Wita, Lisna; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the influence of transformational leadership and work motivation on employee performance. The research method used is a quantitative approach with a causal design. Data were collected through questionnaires distributed to employees in a service sector organization. The data analysis technique used is multiple linear regression. The results show that transformational leadership and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. This finding emphasizes the importance of the role of leaders in creating work motivation to improve organizational performance. This research is expected to provide theoretical and practical contributions in the field of human resource management.